(untitled) (Journal of Parents and Teachers, 2013)
In this interview we are approaching Frances Riu, a religious salesiano who managed the “Escola Cristiana de Catalunya” between 1976 and 2005. The questions, focused on the educative aspect, are about his biography and his opinion about actual aspects.